Partnering intelligence : creating value for your business by building strong alliances - Dent, Stephen M., 1951- (Palo Alto, Calif. : Davies-Black, 1999)
Partnering intelligence. Know thyself. Overview of the partnership continuum. Assessing stage. Exploring stage...
Keywords: Business; Management; Strategic alliances (Business)